Pengaruh Disiplin Kerja Terhadap Kepuasan Karyawan di PT. Perkebunan Nusantara XI - Nikitha Wahyudi; Suhroji Adha (JURNAL RISET MANAJEMEN (JURMA), 2024)
This research aims to analyze the influence of work discipline on employee performance at PT. Perkebunan Nusantara XI (PG) is located in Prajekan District, Bondowoso Regency. Work discipline is considered crucial in improving employee performance, because high discipline is believed to be positively correlated with increased performance. A quantitative approach with explanatory research methods is used in this research to test hypotheses regarding the causal relationship between these variables. Questionnaires that have been proven to be valid and reliable are used to collect data which is then analyzed using multiple linear regression. The results of this research reveal that work discipline does not have a significant impact on employee performance. In contrast, work environmental factors have a significant influence on employee performance, with a contribution of 35.1% to the observed variation in performance. In addition, it was found that appreciation and remuneration from superiors which were felt to be low influenced work discipline. This study suggests that companies should pay more attention to providing appropriate rewards and ensuring good communication regarding obstacles that can affect employee performance.